LOCALIZATION OF SOUND ON ICE AND SNOW - Silver, Carl A.; Fletcher, John L. (1958)
An attempt was made to investigate the ability of subjects to locate the origin of signals over ice or snow surfaces. Subjects were able to localize the direction of sounds better over snow surface than over ice. It has been demonstrated that localization of sound on snow surfaces is superior to localization on ice surfaces. As an aid to communication, investigation should be made of intelligibility over ice and snow. (Author)